2020
DOI: 10.1002/bdm.2205
|View full text |Cite
|
Sign up to set email alerts
|

Leaving with something: When do people experience an equity–efficiency conflict?

Abstract: When allocating resources, people often have to resolve a conflict between equity and efficiency concerns. That is, sometimes for everyone to receive the same amount of resources, some resources must be used suboptimally. However, it is unclear whether and how people account for the impact their allocation decisions would have on the recipients' outcome. In three experiments, we examine how the amount of resources allocated to the recipients influences allocators' decisions and use mouse tracking techniques to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 68 publications
0
3
0
1
Order By: Relevance
“…Such theories argue against distributive actions that, despite yielding overall beneficial outcomes, contravene moral principles (e.g., maximizing benefits but compromising equality; Gawronski et al, 2017;Greene, 2007a;Hsu et al, 2008;Huang et al, 2020;Rawls, 1971). Therefore, the preference for equality closely resonates with broader deontological moral principles (Gordon-Hecker et al, 2017;Gordon-Hecker et al, 2021) and is considered as a robust deontological moral social norm (Messick, 1993).…”
Section: Allocation Preferences For Equality Versus Efficiency In Hel...mentioning
confidence: 99%
“…Such theories argue against distributive actions that, despite yielding overall beneficial outcomes, contravene moral principles (e.g., maximizing benefits but compromising equality; Gawronski et al, 2017;Greene, 2007a;Hsu et al, 2008;Huang et al, 2020;Rawls, 1971). Therefore, the preference for equality closely resonates with broader deontological moral principles (Gordon-Hecker et al, 2017;Gordon-Hecker et al, 2021) and is considered as a robust deontological moral social norm (Messick, 1993).…”
Section: Allocation Preferences For Equality Versus Efficiency In Hel...mentioning
confidence: 99%
“…Many studies of behavior in strategic games used the so-called "mouse-lab" technique, where certain options or payoffs in the game were hidden behind boxes that the subject had to click on to observe the number. While this approach has yielded many useful observations (such as that in complex games individuals do not explore all possible options (Bigoni, 2010;Bigoni & Fort, 2013;Brocas, Carrillo, & Sachdeva, 2018;Brocas, Carrillo, Wang, & Camerer, 2014;Chen, Huang, & Wang, 2018;Costa-Gomes et al, 2001;Gordon-Hecker, Schneider, Shalvi, & Bereby-Meyer, 2020;Johnson et al, 2002)), some argue that the process of clicking is too invasive and costly for the participants (Glöckner & Betsch, 2008). Eye-tracking is not strongly affected by these considerations, since it is minimally invasive and does not require any additional actions from the subject.…”
Section: Tracking Social Learning and Choice Processesmentioning
confidence: 99%
“…Response times Hutcherson et al, 2015;Johnson et al, 2017;Chen & Krajbich, 2018;Bottemanne & Dreher, 2019;Konovalov & Krajbich, 2019;Hausfeld, Fischbacher, & Knoch, 2020Rubinstein, 2007Piovesan & Wengström, 2009;Arad & Rubinstein, 2012;Rand et al, 2012Rand et al, , 2014Krajbich, Bartling, et al, 2015;Hutcherson et al, 2015;Agranov et al, 2015;Rubinstein, 2016;Bear & Rand, 2016;Rand, 2016 Fosgaard et al, 2020;Teoh et al, 2020Costa-Gomes & Crawford, 2006Knoepfle et al, 2009;Wang et al, 2010;Devetag et al, 2016;Polonio et al, 2015;Stewart et al, 2016;Zonca et al, 2019Zonca et al, , 2020Hausfeld, von Hesler, & Goldlücke, 2020;Teoh et al, 2020Knoepfle et al, 2009 Mousetracking Brocas et al, 2014;Hausfeld, Fischbacher, & Knoch, 2020;Gordon-Hecker et al, 2020Costa-Gomes et al, 2001Johnson et al, 2002;Bigoni, 2010;Bigoni & Fort, 2013;B...…”
Section: Preferencesunclassified
“…By doing this, individuals can create environments where individuals can leverage differences in perspective(Gordon-Hecker et al, 2021). Indeed, in context of Pakistan,Sajid et al (2022) demonstrated teachers' work-family conflict had an impact on their child's performance, at school, thus showing importance of good management of school tasks in curbing potential conflicts and developing improved academic environment that recognize and celebrate unique contribution that each student brings to learning environment.…”
mentioning
confidence: 99%